A review of benefits and Pre-implementation considerations of e-CRM: Exploring the Advantages and Considerations of e-CRM Implementation (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Customers' Relationship Management (ECRM) is the most recent paradigm in the field. As moreand more firms go online, electronic customer relationship management (ECRM) is becoming moreimportant. A company's conventional brick-and-mortar methods are no longer sufficient for web-enabledbusinesses. As a result, these businesses must keep up with the times rather than lag behind them.Papers like this one promote ECRM, examine its advantages, and identify the issues that must beaddressed before its adoption.